Teknologi Biosoildam untuk Mendukung Sistem Agro Konservasi pada Tanah Laterit - Nugroho Widiasmadi (Departement of Mathematics Education, 2023)
The objective of this analysis is to improve soil infiltration rate on Laterit agroland with biofertilizer MA-11 on the Biosolids. As a control is original soil without microbial activity triggered. The research was carried out in July to Agustus 2021 at an area of shallot agroland in Blora Districts. The research was to use a double ring infiltrometer to measure soil infiltration with three replications on each distance from Biohole and use electrolyte conductivity meter (EC) to measure soil fertility by salt ion concentration and soil acidity. The measurement was done every five minutes and observation period every fifteen days along forty five days. The results of research show that the highest of infiltration rate, infiltration capacity , fertility & acidity happened on soil which involved Biofertilizer MA-11. The infiltration rate shows a constant value at a level of 57 to 98 cm / hour which is achieved after the 29 th day. Meanwhile, the EC value in stable conditions is achieved on the 29th day with a value between 535 - 785 uS / cm. So that the activity of biological agents on Andosol soil with the infiltration level will be optimal on day 31